Gambaran Pemanfaatan Pelayanan Kesehatan Tradisional pada Penduduk Lanjut Usia di Indonesia - Rukmini Rukmini; Lusi Kristiani (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2021)
One of the health efforts that have the opportunity to improve the health status of the elderly is traditional health services (Yankestrad). This paper aims to describe the use of Yankestrad among the elderly in Indonesia. The data source in this analysis is Riskesdas 2018, a research conducted by the Ministry of Health with the elderly (≥60 years) as the analysis unit. Data were analyzed descriptively. The results showed that the use of Yankestrad in the elderly was 37.0% and self-medication with traditional medicine was 17.3%. Young elderly people mostly use Yankestrad (37.9%), while self-medication with traditional medicine are dominated by elderly women (18.3%) in rural areas (19.5%). The use of Toga in the elderly in Indonesia (31.9%), mostly women (33.3%) in rural areas (36.3%). The most common types of Yankestrad used by the elderly were manual skills, potions, and homemade potions. Male elderly (55.5%) in urban areas (56.5%) used more prepared ingredients, while female elderly (43.6%) in rural areas (46.5%) preferred homemade ingredients. Older people with low expenditure levels tend to take advantage of prepared ingredients or homemade ingredients, while high expenditures tend to take advantage of manual skills. Traditional healers (98.2%) are the type of yakestrad used mostly by the elderly. In conclusion, Yankestrad in Indonesia is mostly used by the elderly, therefore it has the potential to be developed as an alternative model of health services for the elderly. Given the high interest of the elderly with Yankestrad and the use of traditional healers, it is necessary to provide Yankestrad facilities, especially in Puskesmas with traditional health workers who are able to provide safe and quality health services to the elderly. Abstrak Salah satu upaya kesehatan yang berpeluang meningkatkan status kesehatan lansia adalah pelayanan kesehatan tradisional (Yankestrad). Tulisan ini bertujuan untuk mengetahui gambaran pemanfaatan Yankestrad pada penduduk lansia di Indonesia. Sumber data dalam analisis ini adalah Riskesdas 2018. Riset yang dilakukan oleh Kementerian Kesehatan dengan unit analisis lansia (≥60 tahun). Analisis data secara deskriptif. Hasil menunjukkan, pemanfaatan Yankestrad pada lansia 37,0% dan upaya sendiri dengan obat tradisional 17,3%. Lansia muda terbanyak memanfaatkan Yankestrad (37,9%), sedangkan upaya sendiri dengan obat tradisonal didominasi lansia perempuan (18,3%) di perdesaan (19,5%). Pemanfaatan Toga pada lansia di Indonesia (31,9%), terbanyak perempuan (33,3%) di perdesaan (36,3%). Jenis Yankestrad terbanyak dimanfaatkan lansia adalah keterampilan manual, ramuan jadi dan ramuan buatan sendiri. Lansia laki-laki (55,5%) di perkotaan (56,5%) lebih banyak memanfaatkan ramuan jadi, sedangkan lansia perempuan (43,6%) di perdesaan (46,5%) lebih menyukai ramuan buatan sendiri. Lansia dengan tingkat pengeluaran rendah cenderung memanfaatkan ramuan jadi atau ramuan buatan sendiri, sedangkan pengeluaran tinggi cenderung memanfaatkan ketrampilan manual. Penyehat tradisional (98,2%) adalah jenis tenaga terbanyak dimanfaatkan lansia. Kesimpulan, Yankestrad di Indonesia lebih banyak dimanfaatkan oleh lansia, oleh karena itu berpotensi untuk dikembangkan sebagai alternatif model pelayanan kesehatan bagi lansia. Rekomendasi, mengingat tingginya minat para lansia dengan Yankestrad dan pemanfaatan penyehat tradisional, maka diperlukan penyediaan fasilitas Yankestrad khususnya di Puskesmas dengan tenaga kesehatan tradisional yang mampu memberikan pelayanan kesehatan yang aman dan berkualitas bagi para lansia.